Cultura organizacional: sua influência em uma empresa de tecnologia da informação - Jahn, Vitor Ogliari (2023)
This paper proposes an in-depth analysis of organizational culture at SGMobile, an information technology company, highlighting its interaction with organizational climate, leadership, and business motivation. Inspired by Schein's approach (1984), which emphasizes understanding culture beyond visible elements, the study investigates how culture naturally forms in groups or is shaped by leadership. By focusing on SGMobile as a case study, the work aims to comprehend the predominant culture in the company, assess the influence of leadership on its formation and dissemination, and provide practical suggestions for enhancing this culture. The research reveals a robust organizational culture at SGMobile, centered on service excellence and customer relationships, influenced by the CEO's background. Despite the identified strengths, the study emphasizes challenges, such as the need to explicitly clarify leadership's influence on culture, and suggests tangible improvements, such as meetings to reinforce values. Partners acknowledge the importance of investing in specific training, especially in sales, envisioning a future culture with a focus on strategic hiring and internal promotion. By pointing out challenges like resistance to change and recognizing the active involvement of employees in promoting culture, the paper underscores the need for adaptive strategies. In summary, the study not only highlights SGMobile's strengths but also provides a detailed view of areas requiring attention and proposes concrete suggestions to strengthen and further develop its organizational culture.